GE_GERICHTE C/28709/2011 vom 19. März 2014 - GE Cour de justice (2014)
MOTIF; RÉSILIATION; CONTRAT DE TRAVAIL; JUSTE MOTIF; RÉSILIATION IMMÉDIATE; CERTIFICAT DE TRAVAIL | CO.337.1; Cst.9; CPC.247.1; CO.328; CO.337.2; CO.337.D.1; CO.330.A